Silesian Language or Dialect: Why Do We Need a Standard? - Bartkowiak-Lerch, Magdalena (Rocznik Polsko-Niemiecki, 2022)
The article’s goal is to reﬂect on the history of the regional identity of the Upper Silesian region of Poland. Although historical, political, and cultural aspects are considered, the focus is on the linguistic dimension, since language is one of the most important elements of collective identity. The article opens with a short historical overview, starting with the period of the Industrial Revolution, which was the crucial moment for the formation of the so-called Upper Silesian mixed code which is the subject of reﬂection in this article. Next, we analyse the status of the Silesian ethnolect and the possibility of raising it to the rank of a regional language. The investigation is conducted from the point of view of Polish linguistics, but based on a wider perspective of European minority language politics.